Conversion factors of effective and equivalent organ doses with the air kerma area product in patients undergoing coronary angiography and percutaneous coronary interventions. (October 2017) - Brambilla, M.; Cannillo, B.; Matheoud, R.; Compagnone, G.; Rognoni, A.; Bongo, A.S.; Carriero, A.
Highlights: E/KAP and HT /KAP conversion factors reliably predicts E and HT in patients. E/KAP and HT /KAP conversion factors do not depend on patient's sex or weight. E/KAP and HT /KAP may depend on the procedure protocol adopted in different centers. ICRP 103 based E/KAP is 30% higher than E/DAP previously estimated with ICRP 60. Abstract: To derive effective dose (E), organ dose (HT ) and conversion factors with the air kerma area product (KAP) in coronary angiography (CA) and percutaneous coronary intervention (PCI) by the radial route, using the ICRP 103 tissue weighting factors. The study included 34 patients referred for CA and 31 for PCI. E and HT were derived from in-the-field KAP measurements using Montecarlo methods. Median KAP of 23.2 and 56.8 Gy cm 2 and E of 6.9 and 20.0 mSv were found for CA and PCI, respectively. Mean KAP and E were significantly higher in males than in females (52.4 ± 40.0 vs 32.3 ± 16.6 Gy cm 2 ; p = 0.02) and (16.8 ± 13.6 vs 10.7 ± 5.8 mSv; p = 0.04). KAP (r = 0.39; p = 0.001) and E (r = 0.34; p = 0.005) showed a significant correlation with the patient's weight. Conversion factors between KAP and E (E/KAP) were 0.30 ± 0.04 mSv Gy −1 cm −2 for CA and 0.33 ± 0.05 mSv Gy −1 cm −2 for PCI. No significant differences in the E/KAP between males and females were found (0.31 ± 0.05 vs 0.33 ± 0.05; p = 0.08). Again, no significant correlation was found between E/KAP and patient's weight (r = 0.23; p = 0.07). The correlation between E and KAP was excellent for CA (r = 0.99) and PCI (r = 0.96). The correlation between HT and KAP ranged from r = 0.87 to r = 1 and from r = 0.71 to r = 0.98 for CA and PCI, respectively. A single factor, the total KAP, could be used for a specific acquisition protocol to reliably estimate E and HT without the need of a patient's specific analysis. Conversion factors might be installation, X-ray beam quality or protocol dependent.